Effecf of arganic matter, simple superphosphate and potassium chloride on the formation of seedlings of the yellow passion fruit - Peixoto, José Ricardo; Pádua, Thadeu de (Pesquisa Agropecuaria Brasileira, 2014)
This study was conducted to verify the effect of organic matter (manure), simple superphosphate and potassium chloride on the formation of seedlings of the yellow passion-fruit (Passiflora edulis f. flavicarpa Deneger). The experiment was carried out in one of the seedling nurseries of ESAL, In Lavras, MG, Brazil, from September to November of 1984. The experimental design used was completely randomized in a 4 x 4 x 3 factorial scheme, the factors being four dosages of organic matter (0; 100; 200 e 300 l/m³ of soil), four dosages of simple superphosphate (0,0; 3,0; 6,0 e 9,0 kg/m3 of soil) and three dosages of potassium chloride (0,0; 0,5 e 1,0 kg/m³ of soil) and with three replicates giving a total of 49 treatments and 144 plots, each plot comprising six polyethylene bags. The seedlings were removed 70 days after sowing in order to carry out the assessments. Increase in the dosagens of organic matter and simple superphosphate caused increases in the values of the growth characteristics compared to the untreated controls. Increases in the dosages of potassium chloride caused decreases in the values of dry matter weight of the root system compared to the untreated controls.